Fiscal Policy and the Current Account : Are Microstates Different? - Endegnanew, Yehenew (IMF Working Papers; Working Paper ;, 2012)
This paper examines the empirical link between fiscal policy and the current account focusing on microstates defined as countries with a population of less than 2 million between 1970 and 2009. The paper employs panel regression and panel vector autoregression (VAR) on 155 countries of which 42 are microstates. Panel regression results show that a percentage point improvement in the fiscal balance improves the current account balance by 0.4 percentage points of GDP. The real effective exchange rate has no significant impact on the current account in microstates but the coefficient is significant in the global sample. Panel VAR results show that an increase in government consumption results in real exchange appreciation but the effect on the current account after an initial deterioration dies out quicker in microstates than in the global sample. The result implies that fiscal policy has little effect on the current account in microstates beyond its direct impact on imports. Overall, the results suggest that the weak relative price effects make the effect of fiscal adjustment on the current account much more difficult in microstates.